Impact on healthcare and operational outcomes of outsourcing to a private value-based provider: analysis of tertiary hospitals in the Community of Madrid - Caramés, Cristina; Arcos, Javier; Pfang, Bernadette; Cristóbal, Ion; Álvaro de la Parra, Juan Antonio (Frontiers in Public Health, 2025)
IntroductionOutsourcing to private healthcare providers is a topic of intense debate and with contradictory results published in the literature.MethodsIn this study, we aimed to analyze the effects of outsourcing to a private provider that follows a value-based model on official indicators of quality, functioning and accessibility, safety, and patient experience recently published by the Madrid regional health system for the year 2023.ResultsNotably, we found that the study hospital showed lower mortality rates, surgical and medical complications, and hospital-acquired infections than its peers. Moreover, the study hospital had significantly shorter length of stay and surgical backlog, highlighting its high levels of functioning and accessibility. Regarding patient satisfaction with the care received, the study hospital showed a significantly higher satisfaction index than the control group. Accordingly, the indicator of free choice of medical care available in the Community of Madrid showed that it was a net importer of patients from other tertiary hospitals included in this study.DiscussionOur findings support the idea that outsourcing to value-based healthcare providers represents a valid alternative that does not compromise the overall quality of healthcare offered to patients. On the contrary, this strategy could not only improve indicators but also reveal potential initiatives that will contribute to improving outcomes in public hospitals, creating a positive synergistic loop.